Atypical Presentation of Low-Grade Small Lymphocytic Lymphoma of the Lacrimal Sac. Issue 6 (November 2015) - Papastefanou, Vasilios P.; René, Cornelius; O'Donovan, Dominic G.; Dean, Andrew F.; Wright, Penny A.
Abstract : Lymphoma of the lacrimal sac is uncommon and usually presents as a lacrimal sac mass, against a background of known systemic lymphoma. This study presents the case of a 70-year-old man with small lymphocytic lymphoma of the lacrimal sac and widespread systemic involvement presenting as common canalicular obstruction without a palpable mass or systemic symptoms.